Phycocyanin synthesis and degradation in the blue-green bacterium Anacystis nidulans. - Lau, R H (1977)
Cellular content and rates of synthesis of the apoprotein subunits of phycocyanin in Anacystis nidulans cultures undergoing, and recovering from, nitrate starvation were measured by sodium dodecyl sulfate-polyacrylamide gel electrophoresis of total and immunoprecipitable soluble proteins. Results indicated that (i) nitrate starvation provokes coordinate degradation of apoprotein subunits: (ii) de novo synthesis of these subunits is selectively depressed during starvation; (iii) nitrate restoration provokes coordinate increases in the rates of synthesis of these subunits, although maximal rates are not achieved for 6 to 10 h after readdition of nitrate; and (iv) illumination affects both relative and absolute rates of apoprotein formation.